(Re-)presenting Islam: A comparative study of groups of comedians in the United States of America and France. (1st December 2013) - Ervine, Jonathan
Over the last few years, humour has provided many Muslims with a means of seeking to establish a positive sense of self-identity, as well as a means of challenging misconceptions and fears of Islam in a wide variety of countries on both sides of the Atlantic. This article brings together two interviews with performers who use comedy to engage with perceptions of Islam and (re-)present Muslims in a generally non-threatening and everyday context. It compares and contrasts atrio of American stand-up comedians who tour under the name 'Allah Made Me Funny' and the two French performers who created 'À part ça tout va bien'/'Apart from that everything's fine', a humorous web series in France. The interviews provide an insight into processes of identity negotiation and (re)presentation by performers based in countries with very differing approaches to multiculturalism and diversity.